High-strength anti-stamping PP composite material and preparation method thereof
By using sepiolite fibers loaded with nanotitanium dioxide as modifiers, the problem of insufficient strength and wear resistance in stationery manufacturing is solved, and the strength and wear resistance of polypropylene composite materials are significantly improved.
Patent Information
- Application Number
- CN202411671751.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-21
- Publication Date
- 2025-02-07
- Estimated Expiration
- 2044-11-21
AI Technical Summary
Polypropylene has low strength and poor wear resistance in stationery manufacturing, resulting in the product being easily damaged during long-term use or accidental collisions, and its aesthetics are reduced.
Sepiolite fibers loaded with nanotitanium dioxide are used as modifiers, and reacted with sepiolite fibers and nanotitanium dioxide through grafting agents to form a load connection to improve the strength and wear resistance of polypropylene.
It significantly improves the strength and wear resistance of polypropylene composite materials, and can better meet the requirements of high-end stationery.
Smart Images

Figure CN119391082A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of materials, and in particular to a high-strength and anti-punch PP composite material and a preparation method thereof. Background Art
[0002] In the modern stationery manufacturing industry, composite materials are highly favored due to their unique performance advantages. Stationery is an indispensable tool for daily study and office work, and its quality, durability and feel directly affect the user's experience and efficiency. Polypropylene (PP for short) is a colorless, odorless, non-toxic thermoplastic plastic with the characteristics of low density, light weight, chemical corrosion resistance, good insulation performance, and easy processing. Because of its excellent physical properties, chemical stability and relatively low cost, it has gradually become one of the indispensable composite materials in stationery manufacturing, such as pen holders, pencil cases, folders, folder buckles, etc.
[0003] Stationery products are not only practical tools, but also a reflection of personal taste and style. Therefore, durability and aesthetics are one of the key concerns of consumers. Although polypropylene has relatively excellent comprehensive performance, its strength performance is slightly poor and its wear resistance is not good. It is difficult to maintain its integrity in the case of long-term writing or accidental dropping. It is also impossible to avoid a large number of scratches and wear caused by friction, resulting in a decrease in product aesthetics. Therefore, how to enhance and modify polypropylene so that it can meet the various requirements required for high-end stationery has become a research hotspot.
[0004] The invention patent with publication number CN114507400B discloses a modified glass fiber reinforced polypropylene composition and a preparation method thereof. The medium alkali glass fiber is modified by using oxidized polyethylene wax to obtain the modified medium alkali glass fiber. Using the modified medium alkali glass fiber as an additive can effectively enhance the strength of polypropylene. Therefore, using the fiber as an additive has a positive effect on improving the mechanical strength of polypropylene. However, using the fiber alone as an additive cannot produce a good modification effect on the wear resistance of polypropylene. Based on this, the present invention provides a high-strength and anti-impact PP composite material that can be directly used to manufacture high-end stationery products. Summary of the invention
[0005] In order to solve the problems mentioned in the background technology, the purpose of the present invention is to provide a high-strength and impact-resistant PP composite material and a preparation method thereof.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] A method for preparing a high-strength and anti-impact PP composite material, wherein the PP composite material is made of the following raw materials in parts by weight:
[0008]
[0009] The preparation method comprises the following steps:
[0010] The first step is to weigh each raw material in parts by weight and set aside;
[0011] Step 2: Add polypropylene, modifier, compatibilizer, antioxidant and lubricant into a stirring kettle, control the speed to 1000-2000r / min, the temperature to 100-120°C, mechanically stir and mix for 30-60min, cool and discharge to form a pre-mixed material;
[0012] The third step is to feed the mixed material into a twin-screw extruder and obtain the PP composite material through a melt extrusion granulation process.
[0013] As a further embodiment of the present invention, the preparation method of the modifier comprises the following steps:
[0014] Step 1, dispersing sepiolite fiber in toluene to form a sepiolite fiber dispersion, which is referred to as dispersion 1; dispersing nano titanium dioxide in toluene to form a nano titanium dioxide dispersion, which is referred to as dispersion 2;
[0015] Step 2, add the grafting agent to the dispersion one, and after adding, continue to add the tin metal catalyst, stir evenly, then increase the temperature to 70-80°C, keep stirring for 2-4 hours, reduce the temperature to 40-50°C, and then add the dispersion two, after adding, further increase the temperature to 80-90°C, continue to keep warm for 6-9 hours, centrifuge to separate the solid material, wash and vacuum dry to obtain the modifier.
[0016] As a further solution of the present invention, in step one, the mass fraction of the dispersion one is 20-30%; the mass fraction of the dispersion two is 10-15%.
[0017] As a further solution of the present invention, in step 2, the preparation method of the grafting agent is as follows:
[0018] The terminal hydroxyl nitrile rubber is mixed with tetrahydrofuran, stirred evenly, and then benzoyl chloride modifier and pyridine are added to the obtained uniform liquid material under ice bath conditions. After the addition is completed, the ice bath is removed, and after stirring at room temperature for 6-9 hours, the solvent is evaporated to remove and the material is separated to obtain the grafting agent.
[0019] As a further embodiment of the present invention, the benzoyl chloride modifier is 4-isocyanatobenzoyl chloride or 3-isocyanatobenzoyl chloride.
[0020] As a further embodiment of the present invention, the molar ratio of the hydroxy-terminated nitrile rubber to the benzoyl chloride modifier is 1:2.
[0021] As a further embodiment of the present invention, in step 2, the tin metal catalyst is any one of stannous octoate, dibutyltin diacetate or dibutyltin dilaurate.
[0022] As a further solution of the present invention, in step 2, the volume ratio of dispersion 1 to dispersion 2 is 1:0.2-0.4.
[0023] Specifically, firstly, terminal hydroxyl nitrile rubber and benzoyl chloride modifier are used as reactants, and by controlling the molar ratio of the two, a nitrile rubber derivative with a highly active isocyanate group as the end group, namely, a grafting agent, is prepared. Then, under the action of a tin metal catalyst, the isocyanate group at one end of the grafting agent structure can undergo a grafting reaction with the hydroxyl group on the surface of the sepiolite fiber, and the isocyanate group at the other end can undergo a grafting reaction with nano-titanium dioxide, which is equivalent to using the grafting agent as a connecting substance to achieve a load connection between nano-titanium dioxide and sepiolite fiber, thereby obtaining a modifier.
[0024] As a further solution of the present invention, the compatibilizer is maleic anhydride grafted polyethylene or maleic anhydride grafted polypropylene; the antioxidant is a phosphite antioxidant; and the lubricant is any one of paraffin, polyethylene wax or stearic acid.
[0025] A high-strength and anti-punch PP composite material is prepared by adopting the preparation method.
[0026] Beneficial effects of the present invention:
[0027] The present invention uses sepiolite fiber loaded with nano titanium dioxide as a modifier to modify polypropylene. On the one hand, the grafting agent for realizing the load connection between each other is a nitrile rubber derivative, which has good compatibility with the polypropylene matrix, and therefore, the negative impact caused by poor compatibility between the modifier and the polypropylene matrix can be avoided. On the other hand, since the nitrile rubber is an oily macromolecular substance, the nano titanium dioxide can be urged to slide relatively on the surface of the sepiolite fiber, and a micro ball effect is produced, thereby the wear resistance of the polypropylene composite material can be effectively improved, and due to the load of the nano titanium dioxide, a micro three-dimensional structure is formed on the surface of the sepiolite fiber, and this micro three-dimensional structure can be firmly stuck in the polypropylene matrix to form a firm snap-on structure, thereby enabling the sepiolite fiber to efficiently play an enhanced modification effect, and improve the strength of the polypropylene composite material.
[0028] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0030] Figure 1 These are scanning electron microscope images of sepiolite fiber and modifier, where (A) is sepiolite fiber and (B) is modifier. DETAILED DESCRIPTION
[0031] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Preparation Example
[0033] The preparation method of the modifier comprises the following steps:
[0034] Step 1, dispersing sepiolite fiber in toluene to form a sepiolite fiber dispersion with a mass fraction of 25%, which is recorded as dispersion 1; dispersing nano titanium dioxide in toluene to form a nano titanium dioxide dispersion with a mass fraction of 10%, which is recorded as dispersion 2;
[0035] Step 2: 1.5 g of hydroxy-terminated nitrile rubber with a number average molecular weight of 3500 was mixed with tetrahydrofuran, and after stirring evenly, 0.16 g of 3-isocyanatobenzoyl chloride and 0.2 g of pyridine were added to the obtained uniform liquid material under ice bath conditions. After the addition, the ice bath was removed, and after stirring at room temperature for 8 hours, the solvent was evaporated to remove the solvent, and the material was separated to obtain a grafting agent;
[0036] Step 3: Add the grafting agent to 20 mL of dispersion 1. After adding, continue to add 0.1 g of dibutyltin dilaurate, stir evenly, then raise the temperature to 75 ° C. After stirring for 3 hours, lower the temperature to 45 ° C. and then add 5 mL of dispersion 2. After the addition is completed, further heat to 85 ° C. After continuing to keep warm for 8 hours, centrifuge to separate the solid material, wash and vacuum dry to obtain the modifier.
[0037] Figure 1The figures are scanning electron microscope images of sepiolite fiber and modifier, where (A) is sepiolite fiber and (B) is modifier. It can be seen from the figure that the surface of sepiolite fiber is smooth and flat without obvious protrusions, while the modifier is obviously sepiolite fiber with nano-scale particles loaded on the surface. It can be inferred that the nano-scale particles are nano-titanium dioxide.
[0038] Example 1
[0039] A high-strength and anti-impact PP composite material is made of the following raw materials in parts by weight:
[0040]
[0041] The preparation method of the PP composite material comprises the following steps:
[0042] The first step is to weigh each raw material in parts by weight and set aside;
[0043] Step 2: Add polypropylene, modifier, compatibilizer, phosphite and paraffin into a stirring kettle, control the speed to 1000r / min, the temperature to 120°C, mechanically stir and mix for 60 minutes, cool and discharge to form a pre-mixed material;
[0044] The third step is to feed the mixed material into a twin-screw extruder, control the extrusion temperature to 200°C, and the screw speed to 50rpm, and obtain the PP composite material through a melt extrusion granulation process.
[0045] The compatibilizer is maleic anhydride grafted polypropylene with a grafting rate of 1%. The preparation method of the modifier is shown in the preparation example, and the same applies to the following.
[0046] Example 2
[0047] A high-strength and anti-impact PP composite material is made of the following raw materials in parts by weight:
[0048]
[0049] The preparation method of the PP composite material comprises the following steps:
[0050] The first step is to weigh each raw material in parts by weight and set aside;
[0051] Step 2: Add polypropylene, modifier, compatibilizer, phosphite and stearic acid into a stirring kettle, control the speed to 1500r / min, the temperature to 110°C, mechanically stir and mix for 40 minutes, cool and discharge to form a pre-mixed material;
[0052] The third step is to feed the mixed material into a twin-screw extruder, control the extrusion temperature to 200°C, and the screw speed to 50rpm, and obtain the PP composite material through a melt extrusion granulation process.
[0053] Example 3
[0054] A high-strength and anti-impact PP composite material is made of the following raw materials in parts by weight:
[0055]
[0056] The preparation method of the PP composite material comprises the following steps:
[0057] The first step is to weigh each raw material in parts by weight and set aside;
[0058] Step 2: Add polypropylene, modifier, compatibilizer, phosphite and polyethylene wax into a stirring kettle, control the speed to 2000r / min, the temperature to 120°C, mechanically stir and mix for 30 minutes, cool and discharge to form a pre-mixed material;
[0059] The third step is to feed the mixed material into a twin-screw extruder, control the extrusion temperature to 200°C, and the screw speed to 50rpm, and obtain the PP composite material through a melt extrusion granulation process.
[0060] Comparative Example 1
[0061] A high-strength and anti-impact PP composite material is made of the following raw materials in parts by weight:
[0062]
[0063]
[0064] The preparation method of the PP composite material comprises the following steps:
[0065] The first step is to weigh each raw material in parts by weight and set aside;
[0066] Step 2: Add polypropylene, sepiolite fiber, compatibilizer, phosphite and stearic acid into a stirring kettle, control the speed to 1500r / min, the temperature to 110°C, mechanically stir and mix for 40 minutes, cool and discharge the material to form a pre-mixed material;
[0067] The third step is to feed the mixed material into a twin-screw extruder, control the extrusion temperature to 200°C, and the screw speed to 50rpm, and obtain the PP composite material through a melt extrusion granulation process.
[0068] Comparative Example 2
[0069] A high-strength and anti-impact PP composite material is made of the following raw materials in parts by weight:
[0070]
[0071] The preparation method of the PP composite material comprises the following steps:
[0072] The first step is to weigh each raw material in parts by weight and set aside;
[0073] Step 2: Add polypropylene, compatibilizer, phosphite and stearic acid into a stirring kettle, control the speed to 1500r / min, the temperature to 110°C, mechanically stir and mix for 40 minutes, cool and discharge the material to form a pre-mixed material;
[0074] The third step is to feed the mixed material into a twin-screw extruder, control the extrusion temperature to 200°C, and the screw speed to 50rpm, and obtain the PP composite material through a melt extrusion granulation process.
[0075] Test Case
[0076] The PP composite materials prepared in the examples and comparative examples were made into test samples that met the test specifications, and various performance tests were performed. The results are shown in the following table:
[0077] Table 1 - Results of various performance tests
[0078] Tensile strength / MPa <![CDATA[Impact strength / kJ / m 2 > Wear amount / g Example 1 38.4 34.8 0.04 Example 2 39.0 35.1 0.03 Example 3 38.9 34.6 0.03 Comparative Example 1 34.1 29.0 0.10 Comparative Example 2 29.5 22.5 0.11
[0079] The test method for tensile strength refers to the standard GB / T 1040-1992; the test method for impact strength refers to the standard GB / T 1843-2008; the test method for abrasion refers to the standard ASTM D3884.
[0080] From the test results in Table 1, it can be seen that the use of the modifier in the preparation example to modify polypropylene can make the prepared composite material exhibit excellent mechanical strength and also excellent wear resistance.
[0081] After replacing the composite material with sepiolite fiber, the reinforcing modification effect of the sepiolite fiber cannot be fully exerted due to the problem of interface incompatibility, and since the ball effect cannot be produced, the mechanical strength and wear resistance of the composite material are reduced.
[0082] After the modifier is completely removed, the fiber reinforcement effect is lost and the mechanical strength of the composite material is further reduced.
[0083] Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core ideas, including the best mode, and also enable any technician in the field to practice the present invention, including making and using any device or system, and implementing any combined method. It should be pointed out that for ordinary technicians in this technical field, without departing from the principle of the present invention, the present invention can also be improved and modified, and these improvements and modifications also fall within the scope of protection of the claims of the present invention. The scope of patent protection of the present invention is defined by the claims and may include other embodiments that can be thought of by those skilled in the art. If these other embodiments have structural elements similar to the literal expression of the claims, or if they include equivalent structural elements that are not substantially different from the literal expression of the claims, then these other embodiments should also be included in the scope of the claims.
[0084] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing a high-strength and anti-impact PP composite material, characterized in that: The PP composite material is made of the following raw materials in parts by weight: The preparation method comprises the following steps: The first step is to weigh each raw material in parts by weight and set aside; Step 2: Add polypropylene, modifier, compatibilizer, antioxidant and lubricant into a stirring kettle, control the speed to 1000-2000r / min, the temperature to 100-120°C, mechanically stir and mix for 30-60min, cool and discharge to form a pre-mixed material; The third step is to feed the mixed material into a twin-screw extruder and obtain the PP composite material through a melt extrusion granulation process.
2. The method for preparing a high-strength and anti-impact PP composite material according to claim 1, characterized in that: The preparation method of the modifier comprises the following steps: Step 1, dispersing sepiolite fiber in toluene to form a sepiolite fiber dispersion, which is referred to as dispersion 1; dispersing nano titanium dioxide in toluene to form a nano titanium dioxide dispersion, which is referred to as dispersion 2; Step 2, add the grafting agent to the dispersion one, and after adding, continue to add the tin metal catalyst, stir evenly, then increase the temperature to 70-80°C, keep stirring for 2-4 hours, reduce the temperature to 40-50°C, and then add the dispersion two, after adding, further increase the temperature to 80-90°C, continue to keep warm for 6-9 hours, centrifuge to separate the solid material, wash and vacuum dry to obtain the modifier.
3. The method for preparing a high-strength and anti-impact PP composite material according to claim 2, characterized in that: In step 1, the mass fraction of the dispersion 1 is 20-30%; the mass fraction of the dispersion 2 is 10-15%.
4. The method for preparing a high-strength and anti-impact PP composite material according to claim 2, characterized in that: In step 2, the preparation method of the grafting agent is as follows: The terminal hydroxyl nitrile rubber is mixed with tetrahydrofuran, stirred evenly, and then benzoyl chloride modifier and pyridine are added to the obtained uniform liquid material under ice bath conditions. After the addition is completed, the ice bath is removed, and after stirring at room temperature for 6-9 hours, the solvent is evaporated to remove and the material is separated to obtain the grafting agent.
5. The method for preparing a high-strength and anti-impact PP composite material according to claim 4, characterized in that: The benzoyl chloride modifier is 4-isocyanatobenzoyl chloride or 3-isocyanatobenzoyl chloride.
6. The method for preparing a high-strength and anti-impact PP composite material according to claim 4, characterized in that: The molar ratio of the hydroxy-terminated nitrile rubber to the benzoyl chloride modifier is 1:
2.
7. The method for preparing a high-strength and anti-impact PP composite material according to claim 2, characterized in that: In step 2, the tin metal catalyst is any one of stannous octoate, dibutyltin diacetate or dibutyltin dilaurate.
8. The method for preparing a high-strength and anti-impact PP composite material according to claim 2, characterized in that: In step 2, the volume ratio of the dispersion 1 to the dispersion 2 is 1:0.2-0.
4.
9. The method for preparing a high-strength and anti-impact PP composite material according to claim 1, characterized in that: The compatibilizer is maleic anhydride grafted polyethylene or maleic anhydride grafted polypropylene; the antioxidant is a phosphite antioxidant; and the lubricant is any one of paraffin wax, polyethylene wax or stearic acid.
10. A high-strength and anti-impact PP composite material, characterized in that: The method is prepared according to any one of claims 1 to 9.
Citation Information
Patent Citations
A modified glass fiber reinforced polypropylene composition and its preparation method
CN114507400B
Polypropylene composite material and preparation method thereof
CN114196105A
Sepiolite-nano titanium dioxide composite modified PP material and preparation method thereof
CN115926315A
High-strength PVC (polyvinyl chloride), preparation method and cable protection tube
CN118165434A